ANALISIS BIOPOLITIK DAN KONTROL POPULASI PENDUDUK MELALUI PROGRAM KELUARGA BERENCANA DI KOTA SAMARINDA - Syahrin, Muhammad Najeri Al; Al Farauqi, Mochamad Dziqie Aulia; Jamal, Sri Wahyuni (JPP (Jurnal Politik Profetik), 2020)
The population has increased dramatically in recent years, including in Samarinda, East Kalimantan. Ironically, the large population is not supported by the quality of life. This problem makes the government strive to discipline the community in a nonviolent way through the Keluarga Berencana (KB) program. These efforts are manifested in the policy mechanism which links the health science and political social aspects (biopolitics). The effort to control the population is not only because of the health policy’s interest but also as a political-strategic policy. The purpose of this study is providing an analysis of Keluarga Berencana program as the strategy to overcome the health issues and as the implementation of biopolitics. This research uses quantitative methods using document-based literature studies and interviews. In Samarinda, the government has synergized policies and budgets at all level of government, in the form of activities and programs for the establishment of Keluarga Berencana village, decreased the fertility rate, increased number of contraceptive prevalence rate, cooperation and coordination with the Provincial BKKBN and the ministry of health, as well as increasing the quality and quantity of PLKB/PKB, involving Babinsa Koramil and providing free Keluarga Berencana program activities. These activities is an implementation of biopolitical policy to control the population. If there is an imbalance between the population and the burden and ability of the state, then the country will slowly go to the more complex social problems.